PENERAPAN SUPERVISI UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM PEMBELAJARAN KOOPERARTIF DI SMP NEGERI 1 YOGYAKARTA - , Conny ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is based on a fact that SMP Negeri 1 Yogyakarta got the 3rd rank in national exam for Yogyakarta District. As a result, this state secondary school becomes a main choice for parents to send their children to this school. Scores test on natural science, biology for odd semester 2011/2012, for Class VIIIC shows that only 14 (42,42%) of 33 students hit the Minimum Mastery Criteria (MMC) as set standard this subject-the set standard is 70- while 19 or 57,58% of the students did not. Classically, the result of the tests on the subject did not hit the set standard. Theoretically, supervision can enhance the cooperative learning process and the learning results. It can enhance teacherâs ability in cooperative learning process activities and students learning results. Therefore, this action research is conducted with the aim to enhance teacherâs ability in doing the cooperative learning process, the response of students and the teacher, and studentsâ learning results through cooperative learning by means of supervision. This action research is conducted to prove if supervision is able to increase teacherâs ability in the cooperative learning process and to enhance studentsâ learning results through cooperative learning. Research subject is natural science teacher of grade VIIIC applying the cooperative learning in teaching biology. Data is obtained through observation, interviewing teacher and students, studying documents to get the data of learning process, filling up questionnaire to know the teacher and students response, pretest and posttest to the students to know the variance of learning results of cooperative learning. Data is analyzed after conducting the action research. Test to the action research which was done through three cycles supervision shows that there is an enhancement in learning activity 30,7%, and cooperative learning process 29,58%. This enhancement has positive effect on teacherâs knowledge and response and the students response and learning results. The increase is that teacherâs knowledge 12,5%, teacherâs response 13,19%, students response 7,93%, students learning results 37,12%. Classical mastery learning is increased by 82,89 in average, individual mastery 100%. The conclusion is that the application of supervision is able to enhance teacherâs ability in cooperative learning and learning results in SMPN 1 Yogyakarta.